Use of an audio-paced incremental swimming test in young national-level swimmers - Turner, A. P.; Smith, T.; Coleman, S. G. S. (International Journal of Sports Physiology and Performance, 2008)
To evaluate the reliability and sensitivity to training of an audio-paced incremental swimming test. Methods: Eight young national-level male swimmers (age 15 ± 1 year) performed a 7 × 200-m incremental swimming test (velocities 1.19, 1.24, 1.28, 1.33, 1.39, and 1.45 m/s and maximal sprint pace) using an audio-pacing device. The same test was performed 4 times by each participant, 1 wk apart to assess reliability (WK1, WK2) and after 9 and 20 wk of training (WK9, WK20). Blood lactate concentration ([La-]) and heart rate (HR) were recorded after each stage. Outcome measures were the velocity (v) and HR at lactate markers of 2 mM, 4 mM, and D1 mM. Results: Velocities at the lactate markers proved to be more reliable than HR, with typical errors ranging from 0.66% to 2.30% and 1.28% to 4.50%, respectively (shifts in mean ranged -0.91% to 0.73% and -0.84% to 1.79%, respectively). Across WK1, WK9, and WK20 there were significant improvements in peak velocity (P < .001) and each of the velocities associated with the lactate markers (P < .05), whereas only HR at D1mM improved (P < .05). Conclusions: This article demonstrates that an audiopaced incremental swimming test is reliable for use with junior swimmers and is sensitive to changes observed after training. The postswimming measurement of HR in the pool was comparatively less reliable.